Enhanced mass transfer of pulsed vacuum pressure pickling and changes in quality of sour bamboo shoots - Dai, Jian-Wu; Zhang, Qing; Li, Ming; Li, Lian-Jie; Xu, Li-Jia; Liu, Yao-Wen; Yin, Peng-Fei; Liu, Shu-Xiang; Zhao, Yong-Peng; Gou, Kai-Yun; Li, Ying-Lu; Qin, Wen (Frontiers in Microbiology, 2022)
Sour bamboo shoot is a traditional Chinese fermented vegetable food. The traditional pickling method of sour bamboo shoots has the disadvantages of time-consuming, inhomogeneous and difficult to control. Pulsed vacuum pressure pickling (PVPP) technology uses pulsed vacuum pressure to enhance the pickling efficiency significantly. To demonstrate the effects of salt content and PVPP technical parameters on the fermentation of bamboo shoots, the sample salinity, pH value, color, fragility and chewiness, nitrite content and lactic acid bacteria content during pickling process are investigated. The salt content inside bamboo shoots gradually increases to the equilibrium point during the pickling process. The pickling efficiency of bamboo shoots under PVPP technology increased by 34.1% compared to the traditional control groups. Meanwhile, the salt distribution uniformity under PVPP technology also obtains a better performance in comparison with the traditional groups. The pH value decline slowly from 5.96 to 3.70 with the extension of pickling time and sour flavor accumulates step by step. No significant differences are found in the color values (L*, a* and b*) and fragility of bamboo shoot under different salt solution concentration, vacuum pressure and pulsation frequency ratio conditions. CFU of LAB decreases firstly and then increases until the 6th day, followed by a declining trend in volatility. The nitrite content of bamboo shoots samples under PVPP treatments has not exceeded the safety standard (<20mg/kg) in the whole fermentation process, which proves the safety of PVPP technology. In conclusion, PVPP technology can safely replace the traditional method with better quality performance. The optimal PVPP processing conditions (i.e., vacuum pressure of 60kPa, 10min vacuum pressure time versus 4min atmospheric pressure time, salt solution concentration of 6%) have been recommended for pickling sour bamboo shoots with high product quality.